(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2010)
When it comes to basic education in Brazil, many questions have already been studied. Regardless of the approach that underlies the discussions, one of the recurring themes is the quality of education, disproportionate across regions of Brazil. High quality education will only be possible from the moment that public policies are adopted that guarantee equality of access and the permanence of students at school. The aim of this paper is to analyze, based on radical behaviorism, some of the dimensions of today’s educational policies included in the current Educational Development Plan, which are linked to the quality of education and the forms of assessment proposed for its measurement. The dimensions listed for analysis are: continuous progression, assessment, accountability and performance pay. It can be seen that all the issues discussed have a central theme: the power of control, a fact that proves the complexity of the subject matter and the need to understand education as an institution.